KEBIJAKAN PERUBAHAN KURIKULUM DI INDONESIA - Herman, Herman; Lukman Panji, Aji; Eka Mahmud, Muhammad (An-Nadzir : Jurnal Manajemen Pendidikan Islam, 2023)
This research aims to explain the policy of changing the Indonesian education curriculum from 1945 to the present. This curriculum development has been carried out several times in order to make adjustments to changes in technology and information, especially in the field of education. The method used in this research is the library research method. The focus of the study in this journal is on the development of the education curriculum in Indonesia from the beginning of independence to the present. The results showed that the curriculum in Indonesia has changed several times, starting in 1947, 1952, 1964, 1968, 1975, 1985, 1994, 2004, 2013, and last in 2022. The expected benefits of this paper are to provide understanding to teachers and the public regarding curriculum change policies in Indonesia, to be used as a reference for further curriculum development, and to create students who are superior and have global insight.